2009
DOI: 10.1002/jmri.21942
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the walls of saccular cerebral aneurysms with double inversion recovery black‐blood sequence

Abstract: In this study, we evaluated the wall of saccular cerebral aneurysms (SCAs) using two-dimensional double inversion recovery black-blood sequence (BBDI). We examined 14 patients with an unruptured SCA (USCA). The BBDI was peripheral-pulse gated, and was acquired during the mid-diastolic period. We evaluated whether the aneurysmal wall could be visualized with BBDI, and the wall thickness in the neck and dome portion of the aneurysm was measured in cases with acceptable imaging quality. BBDI demonstrated the USCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…Visualization of the aneurysm wall itself has been attempted by using various magnetic fields from 1.5T to 7T. [11][12][13] In these studies, the aneurysm wall thickness showed spatial variation within the aneurysm compared with the wall of the parent artery. The intensity of the wall is equal to the intensity of brain tissue; therefore, it is difficult to achieve complete visualization of the entire wall of the cerebral aneurysm, even by high-resolution MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Visualization of the aneurysm wall itself has been attempted by using various magnetic fields from 1.5T to 7T. [11][12][13] In these studies, the aneurysm wall thickness showed spatial variation within the aneurysm compared with the wall of the parent artery. The intensity of the wall is equal to the intensity of brain tissue; therefore, it is difficult to achieve complete visualization of the entire wall of the cerebral aneurysm, even by high-resolution MR imaging.…”
Section: Discussionmentioning
confidence: 99%
“…However, preliminary results suggest that VW-MR imaging may be a useful technique for evaluating patients with intracranial aneurysms. An initial study 79 used a 2D double inversion recovery VW-MR imaging sequence at 1.5T with a voxel size of 0.5 ϫ 0.6 ϫ 0.3 mm to image the wall of saccular aneurysms, and there have been subsequent studies of the berry aneurysm wall at 3T and 7T.…”
Section: To Determine Which Aneurysm Has Ruptured In Patients With Acmentioning
confidence: 99%
“…In view of the previously published data, spatial resolution has to be well below aneurysm wall thickness to be capable of demonstrating microstructures within the wall. The spatial resolution used in our study was 5.7-13.2 times higher compared with previous in vivo aneurysm wall studies, 10,11,[13][14][15] which was sufficient to visualize the microstructures in vivo for the first time.…”
Section: Discussionmentioning
confidence: 92%
“…In previously published in vivo aneurysm wall imaging studies, depiction of microstructures within aneurysm walls was limited by spatial resolution, [13][14][15] because wall thicknesses ranged from 20 to 500 m. 16,17 To date, there is only 1 report on intracranial vessel wall microstructures delineated with 7T MR imaging using an ultra-high ex vivo 0.11 ϫ 0.11 mm 2 resolution. 18 The study showed excellent correlation with the histopathologic findings.…”
Section: Discussionmentioning
confidence: 99%